TEACHING SIMPLE PAST TENSE IN NARRATIVE TEXT USING ANIMATION MOVIE THROUGH ONLINE LEARNING - Pabayo, Febriyanti Sonya; Rosnija, Eni; Wajdi, Majid (FKIP - Universitas Tanjungpura, 2022)
The paper discusses the effectiveness of teaching simple past tense in narrative text using animation movie to increase students